Artikel Type 2 Diabetes Mellitus (Case Study at Insan Rizkillah Clinic) - Fitria Ardyanti Ramadhani; Widya Hary Cahyati (Asian Journal of Healthcare Analytics, 2023)
Diabetes Mellitus is a public health problem known as the Mother of Disease which is the mother of other diseases such as cardiovascular disease, kidney failure and blindness (American Diabetes Association, 2017). Diabetes Mellitus Type-2 is the most common type of diabetes. Risk factors and prevalence of Type 2 diabetes mellitus include: 1) Dietary factors, such as high-fat and high-carbohydrate foods, 2) Too many thoughts, 3) Obesity, 4) Unbalanced diet, 5) Lack of exercise. This research is a descriptive qualitative research using the method of observation, observation, interviews, study of documents, giving questionnaires and analyzing the results of statistical tests. The research subjects were the people of Sape District who had received treatment at the General Practitioner Insan Rizkillah with a total of 100 people with male and female identities aged between 40-70 years. The frequency of the very high prevalence of Type 2 diabetes mellitus occurs between the ages of 40-50 years with a result of 3.7%, the percentage of the next category occurs at the age of 51-60 years with a result of 2.9% and the third category is between the ages of 61-70 years with yield 3.4%. The results of the data analysis showed that the patient experienced a very significant increase in level.